Correlation of characteristic Ne soft x-ray signal pulse with plasma focus dynamics in the Ne (97.5%)-Kr (2.5%) admixtures of the INTI PF machine at 12 kV - Federico, Apilado Roy; Saw, Sor Heoh; Choon, Pau, Keat Lee; Rajdeep Singh, Rawat; Lee, Sing (IEEE, 2019)
This paper shows the correlation of the characteristic Ne soft X-ray (SXR) signal pulse with computed dynamics of the plasma focus using doped neon in Ne (97.5%)/Kr (2.5%) admixtures. The Lee model code is coupled with a specifically designed correlation excel template. The results show that typically, the characteristic Ne SXR pulse signal starts after the start of the reflected shock (RS) and before the beginning of the pinch. Specifically, in the illustrated shot, the RS phase starts at 3.375 μs while the pinch phase starts at 3.384 μs. The characteristic Ne SXR signal pulse starts at 3.377 μs, which is 2 ns after the start of the RS and 7 ns before the pinch starts. There is a consistent trend of Ne SXR correlation with the computed dynamics in the Ne doped with Kr admixtures up to a doping level of 2.5%.